Government’s Deficiency of Communication and the Impact on Stakeholder’s (Case of Yellow Waste WtE in Albania) - Kekezi, Ana (European Journal of Multidisciplinary Studies, 2018)
This study discusses how waste management and especially Waste-to-Energy (WtE) is an unfamiliar and non-accepted treatment process to citizens and key actors in Albania. The research aim to find out how the government at all levels have approached the communication of this sector, with the scope to increase awareness, disseminate information and build trust among stakeholders and mainly to citizens as the key stakeholder as the government decisions affect their daily lives. The research will intention to identify, explore and analyse the standings and reactions of key stakeholders in WtE process and to witness the impact of government communication policies and practices in the stakeholder’s opposes, actions and resistance. Main challenges of central and local governmental communication on raising awareness and acceptance on WtE and stakeholders’ participation and social movements will be identified under the loop of some engaged theories on this paper